Dynamic analysis and vibration control for a maglev vehicle-guideway coupling system with experimental verification. (1st April 2023) - Sun, Yougang; He, Zhenyu; Xu, Junqi; Sun, Wei; Lin, Guobin
Abstract: Maglev trains are strongly nonlinear, open-loop unstable, and flexible track systems. Vehicle-guideway self-excited vibration, which occurs mainly due to the deflection of the flexible guideway, may take place when a train is levitated on the guideway, even if the train is stationary. In this research, maglev vehicle-guideway coupling vibration is studied by employing the Hopf bifurcation criterion. First, the nonlinear dynamic model is presented with consideration of the flexibility of the guideway. To avoid the massive computations required to solve all the eigenvalues when analyzing system stability, the stability criterion of the Hopf bifurcation for the maglev system is proposed and proven with strict mathematical analysis. Based on the proposed lemma, the bifurcation points of the maglev system are calculated, and the critical points of the coupling vibration are found. Next, the influence law of the parameters of the guideway on the vehicle-guideway coupling vibration is analyzed with theoretical and numerical simulation. Then the influence law and the system stability range of the control parameters are analyzed to suppress the coupled vibration. Finally, the effectiveness of the proposed theory is verified by experiments.